Collaborative Governance Strategy in Sustainable Tourism Development - Maria B. Ringa; Stella Y. Sahetapi; Melda M. Poeh; Darwin Y. Kefi; Victor Patiasina (Univiversitas Dr. Djar Wattiheluw, 2023)
This study aims to discover collaborative governance in managing sustainable tourism in Bajawa. This study uses phenomenology to find meaning that explores quantitative and qualitative research data. This research focuses on government collaboration divided into three processes: Dynamics of collaboration, collaborative actions, and their impact on tourism development. Data collection techniques are interviews, observations, and documentation to the government and tourism actors in 6 (six) sub- districts in Bajawa - Ngada, East Nusa Tenggara Province. The place is prioritized to have various tourist destinations, namely marine tourism, spiritual tourism, historical tourism, nature tourism, and others. Collaborate governance aims to see good collaboration between the government (cross- sectoral agencies), business actors, and the community around tourist destinations. The problem in this research is that there needs to be collaborative governance in sustainable tourism in Bajawa and seeing how the right strategy is in collaborated governance for sustainable tourism development in Bajawa City, East Nusa Tenggara.